Smallholder groundwater irrigation in Sub-Saharan Africa: an interdisciplinary framework applied to the Usangu Plains, Tanzania - Villholth, Karen G.; Ganeshamoorthy, G.; Rundblad, C.M.; Knudsen, T.S. (Springer, 2013)
A simple but comprehensive framework for analysing the potential for and constraints to groundwater development for irrigated agriculture in Sub-Saharan Africa is proposed. The framework, based on food value chain principles, is applied to the sub-Saharan context and a specific catchment in Tanzania, the Usangu plains, where groundwater has been proposed as a strategic resource for augmenting food production and smallholder livelihoods and to alleviate seasonal water scarcity. The novel contribution of the work is the presentation of a tool that can be applied to support an interdisciplinary approach to systematically identify most significant barriers and most critical water management and development interventions for sustainable development of groundwater irrigation. The result of the case study shows that farmer economics, capacity, and pump and well drilling market constraints limit groundwater irrigation in the Usangu plains rather than hydrogeological conditions.